Code Mixing in Yowis Ben Film by Fajar Nugros - Titi Surya Ningrum; Sumarlam Sumarlam; Djatmika Djatmika (Hasanuddin University, 2019)
This research discussed code-mixing in Yowis Ben film from Fajar Nugros which is 80 percent using Javanese language. This paper aims to describe the forms and factors of using code-mixing. This paper is a kind of descriptive qualitative using observation-notification method (Simak-catat). Data in this study are oral data which is using information form. The population is all of the dialogs in Yowis Ben film. The result shows there are code-mixing word form, phrase, baster, word of frequent, and idiom dominantly code-mixing word form from Indonesian language insert to the Javanese language. Factors of using code-mixing are needs for a synonym, Social value, development and identification of new culture, low frequency of words, pernicious homonymy, oversight, and end (purpose and goal).